Hepatitis A Virus 3C Protease Cleaves NEMO To Impair Induction of Beta Interferon - Wang, Dang (American Society for Microbiology, 2014)
NEMO (NF-κB essential modulator) is a bridging adaptor indispensable for viral activation of interferon (IFN) antiviral response. Herein, we show that hepatitis A virus (HAV) 3C protease (3C(pro)) cleaves NEMO at the Q304 residue, negating its signaling adaptor function and abrogating viral induction of IFN-β synthesis via the retinoic acid-inducible gene I/melanoma differentiation-associated protein 5 (RIG-I/MDA5) and Toll-like receptor 3 (TLR3) pathways. NEMO cleavage and IFN antagonism, however, were lost upon ablation of the catalytic activity of 3C(pro). These data describe a novel immune evasion mechanism of HAV.